Synthesis, Antiinflammatory and Antibacterial Activity of Novel Indolyl-isoxazoles - Panda, S. S. (Medknow Publications, 2009)
Chalcones were synthesized by reacting indole-3-aldehyde, prepared by Vilsemeir Haack reaction with 4-substituted acetophenone in ethanolic KOH solution. These chalcones were immediately reacted with hydroxylamine hydrochloride in presence of glacial acetic acid as reagent to obtain the corresponding isoxazole derivatives. The synthesized heterocycles were characterized on the basis of physical, chemical tests and spectroscopic data. These compounds were tested for the acute antiinflammatory activity and antibacterial activity using carrageenan-induced rat paw edema method and cup-plate method, respectively.